ANALYSIS OF INDICATORS AFFECTING THE ORGANIZATIONAL-ECONOMIC STATE OF HOUSING FUND MANAGEMENT - Ne'matillaevich, Kholmuradov Rakhmatilla (Antis Publisher, 2024)
This scientific article shows the existing problems in increasing the efficiency of housing fund management in our country and ways to overcome them, the organization of activities of today's housing fund management companies by types, and the specific features of management. Due to the growth of the population, the need for housing is increasing, the benefits given by the state for the construction of new houses and the repair of existing ones are covered.